New Ways of Teaching Adat (Customary) Law at Indonesian Law Schools - Utama, Tody S.J.; Simarmata, Rikardo; Vel, Jacqueline A.C.; Bedner, Adriaan W. (UI Scholars Hub, 2024)
While customary law typically is not the sole legal system regulating people's daily lives, it still plays a big role in shaping the behavior of countless individuals worldwide. For this reason, law schools in many countries teach customary law courses, but these courses often present customary law as a sterile set of principles and norms detached from studying social reality. This approach associates customary law with traditional communities whose members live in relative isolation from the world, ignoring the fact that customary law operates in a legally pluralistic universe, interacting with religious and state law systems, and that it adapts to new economic and social conditions. This way of teaching customary law is common in Indonesia. The present article discusses the origins of the current situation and the need for innovations in customary law courses in Indonesia. We analyze the current shortcomings and challenges in the existing adat (customary) law courses and propose socio-legal approach to improve their relevance. This new approach aims to equip students with knowledge that has more practical relevance and enhances the course’s doctrinal features. In so doing, we pay tribute to Keebet von Benda-Beckmann’s indefatigable efforts to better understand and recognize the importance of adat in the context of legal pluralism in Indonesia.